2018
DOI: 10.1523/eneuro.0101-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Early Targeting of L-Selectin on Leukocytes Promotes Recovery after Spinal Cord Injury, Implicating Novel Mechanisms of Pathogenesis

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…In the spinal cord, like in many other injured tissues [79], neutrophils are the first cell type to infiltrate into the tissue, peaking 1 day after injury followed by a quick reduction in numbers [80]. Several studies have identified neutrophils as a promising target after SCI [7,81,82]. However, in other studies, neutrophil depletion has led to impaired recovery and increased tissue damage [83].…”
Section: Discussionmentioning
confidence: 99%
“…In the spinal cord, like in many other injured tissues [79], neutrophils are the first cell type to infiltrate into the tissue, peaking 1 day after injury followed by a quick reduction in numbers [80]. Several studies have identified neutrophils as a promising target after SCI [7,81,82]. However, in other studies, neutrophil depletion has led to impaired recovery and increased tissue damage [83].…”
Section: Discussionmentioning
confidence: 99%
“…The proteins S100A8 and S100A9 are frequently combined as the antimicrobial dimer calprotectin (Striz and Trebichavsky, 2004). They probably arrive in the injured spinal cord as constituents of myeloid cells, particularly neutrophils (Fleming et al, 2006; Mitchell et al, 2008), which are thought to be deleterious to recovery (McCreedy et al, 2018), although S100A8 and S100A9 can also be induced in macrophages and microglia by neuropathic states (Abe et al, 1999). While there is some indirect evidence that S100A9 promotes recovery from SCI (Roet et al, 2013), but pro-inflammatory effects are more likely the dominant initial action.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the disruption of circadian outputs persisted beyond 2 dpi, including rhythms of serum CORT, body temperature, and activity (all were disrupted until at least 7 dpi), yet our study only assessed gene expression changes at 2 d postsurgery. Gene expression was assessed at 2 d postsurgery because robust changes in the circadian system were seen at this time, and because early changes in lesion pathology and inflammation likely have strong effects on recovery trajectory (Noble et al, 2002; Kigerl et al, 2009; Gaudet et al, 2018; McCreedy et al, 2018). It is also important, however, to understand how clock and inflammatory gene patterns shift through subacute and chronic times postsurgery.…”
Section: Discussionmentioning
confidence: 99%